FUNERALS AND OFFERINGS: A CEMETERY IN NASCA TIMES IN THE AJA VALLEY, PERU - de La Torre Zevallos, Juan Carlos (2012)
The present report describes the recent findings of a pre-Hispanic cemetery in times Nasca, in the archaeological site of El Trigal, located in the valley of Aja (Nasca, Peru). The social materiality recovered indicates a chronological connection to the denominated period Early Nasca (50/100-350/400 AD). The archaeological registries document a singularity of funeral contexts, from a scarcity of grave goods to findings of dismembered bodies, with evidence of aggression with a weapon and a severed head. They are joined by the discovery of pottery vessels, deposits, hotplates and postholes adjacent to the burials, which indicate their possible association with political-ideological practices (rituals) and/or economic. These findings suggest a reading of asymmetrical relations policy and the exercise of physical violence in Nasca period.